2019
DOI: 10.3389/fonc.2019.00002
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Inhibits the Growth of Ovarian Cancer Cells in vitro and in vivo

Abstract: Celastrol is a natural triterpene isolated from the Chinese plant Thunder God Vine with potent antitumor activity. However, the effect of celastrol on the growth of ovarian cancer cells in vitro and in vivo is still unclear. In this study, we found that celastrol induced cell growth inhibition, cell cycle arrest in G2/M phase and apoptosis with the increased intracellular reactive oxygen species (ROS) accumulation in ovarian cancer cells. Pretreatment with ROS scavenger N-acetyl-cysteine totally blocked the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…The ethanol was then discarded and cleaned with cold PBS before staining with PI (50 µg/ml) for 15 min before being measured by FCM with an excitation wavelength of 480 nm through an FL-2 filter (585 nm). ModFit LT 3.0 software (Becton Dickinson) was used to quantify the date (29,30).…”
Section: Cell Cycle Assaymentioning
confidence: 99%
“…The ethanol was then discarded and cleaned with cold PBS before staining with PI (50 µg/ml) for 15 min before being measured by FCM with an excitation wavelength of 480 nm through an FL-2 filter (585 nm). ModFit LT 3.0 software (Becton Dickinson) was used to quantify the date (29,30).…”
Section: Cell Cycle Assaymentioning
confidence: 99%
“…We have also demonstrated that celastrol was able to enhance the sensitivity of the doxorubicin-resistant colon cancer cells via direct binding to P-glycoprotein1 (P-gp), a multidrug resistance protein belonging to ATP-dependent transporters. Interestingly, a few recent reports have indicated that celastrol has the potential to induce intracellular ROS generation in lung, osteosarcoma, melanoma, and ovarian cancer cells [2023]. This prooxidative activity of celastrol was associated with the induction of cytotoxic effects in these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Celastrol has an efficient anti-cancer property against several cancer types. In ovarian cancer, apoptosis induced by celastrol is mediated by ROS generation [ 202 ]. Additionally, celastrol hinders gastric cancer growth in vivo by modulating a number of cell-cycle and apoptosis-related genes such as CDKN1B [ 203 ].…”
Section: Oncogenic Mirnas Inhibited By Phytochemicals Currently Evmentioning
confidence: 99%